Explaining tonality : Schenkerian theory and beyond - Brown, Matthew, 1957- (Eastman studies in music ;, 2005)
"Matthew Brown's Explaining Tonality: Schenkerian Theory and Beyond considers a number of disparate ways in which functional tonality has been understood. In particular, it focuses on the comprehensive theory developed by Heinrich Schenker in his monumental three-part treatise Neue musikalische Theorien und Phantasien (1906-35)."